Flame-retardant nylon 6 fiber with skin-core structure and preparation method thereof
By adopting a leather core structure design in nylon 6 fibers and using the combination of carbon-forming agent and high-temperature self-crosslinking agent, the problem of insufficient flame retardant performance of nylon 6 fibers in the prior art is solved, and the flame retardant performance is significantly improved while maintaining excellent mechanical properties.
Patent Information
- Application Number
- CN202510117449.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-24
AI Technical Summary
The prior art is difficult to significantly improve the flame retardant properties while maintaining the excellent mechanical properties of nylon 6 fibers, and the durability of traditional flame retardants is not ideal.
The design of the leather core structure is adopted. The carbon-forming agent is located only in the cortical layer, and the high-temperature self-crosslinking agent is located only in the core layer. The carbon-forming agent is arranged in an orderly manner along the axial direction of the fiber. The cross-linking reaction temperature of the high-temperature self-crosslinking agent is higher than the melting point of nylon 6 but lower than its combustion temperature.
In a high-temperature environment, the cortex quickly becomes carbon to block flame and heat. The high-temperature self-crosslinking agent in the core layer undergoes a self-crosslinking reaction when nylon 6 starts to burn, enhancing the structural stability and thermal stability of the fiber, significantly improving the flame retardant performance, while maintaining the high strength of the fiber.
Smart Images

Figure CN119553389B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high-performance fiber materials and relates to a flame-retardant nylon 6 fiber with a skin-core structure and a preparation method thereof. Background Art
[0002] With the development of modern industry, the demand for high-performance fiber materials is growing, especially flame-retardant fibers, which are widely used in clothing, transportation, architectural decoration and other fields. Nylon 6 fiber, as a widely used synthetic fiber, is favored for its excellent mechanical properties, wear resistance and chemical stability. However, the flame retardant properties of pure nylon 6 fiber are limited and it is difficult to meet the application requirements of certain high safety standards. Therefore, it is of great significance to study the flame retardant modification of nylon 6 fiber.
[0003] Traditional flame retardant modification methods, such as adding halogen compounds or phosphorus-containing flame retardants, can improve the flame retardancy of materials to a certain extent, but these additives may affect the mechanical properties of the fiber. In addition, the flame retardant durability of these traditional flame retardants is not ideal, especially after multiple washings or long-term use, the flame retardant performance will decrease.
[0004] In order to overcome these limitations of the prior art, those skilled in the art have been seeking to develop new flame-retardant nylon 6 fiber materials. For example, patent application CN102863611A discloses a high-temperature self-crosslinking expandable flame-retardant anti-melting droplet copolyester based on an azobenzene structure and a preparation method thereof, in which a charring agent and a high-temperature self-crosslinking agent are simultaneously introduced into the copolyester, but the charring agent and the high-temperature self-crosslinking agent are uniformly distributed in the copolyester. The fibers prepared using this copolyester still have the following problems: the high-temperature self-crosslinking agent is also an organic substance, and the high-temperature self-crosslinking agent located on the surface of the copolyester will also burn as a combustible during the combustion process, and will not be able to exert the anti-melting droplet flame retardant function, and will also affect the charring property and char layer quality of the copolyester surface, and will not be able to exert the charring flame retardant function, which ultimately leads to the inability to significantly improve the flame retardant properties.
[0005] Therefore, in order to significantly improve the flame retardant properties of nylon 6 fiber while maintaining excellent mechanical properties, it is necessary to develop a new type of flame retardant nylon 6 fiber. Summary of the invention
[0006] The purpose of the present invention is to solve the above problems existing in the prior art and to provide a flame-retardant nylon 6 fiber with a sheath-core structure and a preparation method thereof.
[0007] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0008] A flame-retardant nylon 6 fiber with a skin-core structure, wherein the base material is nylon 6 and contains a charring agent with a lamellar structure and a high-temperature self-crosslinking agent; the charring agent is only located in the skin layer and is orderly and directional arranged along the axial direction of the flame-retardant nylon 6 fiber with the skin-core structure; the high-temperature self-crosslinking agent is only located in the core layer; the crosslinking reaction temperature of the high-temperature self-crosslinking agent is higher than the melting point of nylon 6 and lower than the combustion temperature of nylon 6; the specification of the flame-retardant nylon 6 fiber with the skin-core structure is 50-150D / 36-96F, and the ratio of the thickness of the skin layer to the diameter of the core layer is 1:6-8.
[0009] During the combustion process of the flame-retardant nylon 6 fiber with a skin-core structure of the present invention, the skin layer burns first and then quickly forms carbon, thereby achieving the effect of blocking flames and suppressing smoke. During this process, heat is conducted from the skin layer to the core layer of the fiber, and the core layer melts and is in a molten state. The cross-linking reaction temperature of the high-temperature self-cross-linking agent in the core layer of the present invention is higher than the melting point of nylon 6, which is conducive to the high-temperature self-cross-linking agent not undergoing a cross-linking reaction during the mixed melt processing of the nylon 6 substrate and the high-temperature self-cross-linking agent. At the same time, the temperature is lower than the combustion temperature of nylon 6, which is conducive to the high-temperature self-cross-linking agent undergoing a self-cross-linking reaction when the nylon 6 starts to burn. Under this effect, the viscosity of the core layer melt increases rapidly, and the melt fluidity decreases, thereby achieving the purpose of flame retardancy and anti-melting dripping.
[0010] The carbonizing agent of the present invention is only located in the cortex. The introduction of a high content of the carbonizing agent will lead to a decrease in the mechanical properties of the fiber. If the carbonizing agent of this content is evenly distributed in the cortex and the core layer, the mechanical strength of the fiber as a whole will be greatly reduced. The present invention controls a large amount of the carbonizing agent to be distributed only in the cortex. Although it will reduce the strength of the cortex to a certain extent, it will promote the distribution of the carbonizing agent with a lamellar structure along the axial direction of the fiber during the fiber drawing process, which can better play the role of inhibiting melt flow and synergistic carbonization. In addition, from the perspective of the entire fiber, the thickness occupied by the cortex is relatively thin, and the strength of the fiber can still be maintained by the core layer, thereby avoiding a decrease in the overall strength of the fiber.
[0011] If the core layer does not have a high-temperature self-crosslinking agent, the flame retardant effect of the carbonizing agent in the skin layer alone cannot achieve the purpose of anti-droplet. The core layer will still melt and form droplets during the combustion process. At the same time, the droplets formed by the core layer will also destroy the carbon layer formed in the skin layer, reducing its flame retardant performance.
[0012] If the high-temperature self-crosslinking agent is evenly distributed in the skin layer and the core layer, since the high-temperature self-crosslinking agent itself will burn as a combustible during the combustion process, it will affect the carbonization of the skin layer and the quality of the carbon layer when the fiber burns, and cannot play its anti-melt droplet function, which is also unfavorable to the flame retardant performance;
[0013] The thickness of the skin layer is designed reasonably to ensure that the heat of carbonization after high-temperature combustion is just enough to cause the core layer to undergo a self-crosslinking reaction; the skin layer cannot be too thick, because the skin layer does not have an anti-dripping effect. If the skin layer is too thick, the skin layer will form droplets due to melting under the flame; the skin layer cannot be too thin, because too thinness will cause heat to be transferred to the core layer too quickly, causing the core layer to melt faster than the crosslinking reaction speed of the high-temperature self-crosslinking agent, thereby affecting the anti-dripping effect.
[0014] As the preferred technical solution:
[0015] A flame-retardant nylon 6 fiber with a skin-core structure as described above, wherein the carbon-forming agent is zirconium phosphate modified by a silane coupling agent;
[0016] The silane coupling agent is γ-methacryloxypropyl trimethoxysilane or γ-glycidyloxypropyl trimethoxysilane. The purpose of the modification is to improve the compatibility of zirconium phosphate with nylon 6 and ensure that the zirconium phosphate is evenly dispersed in the fiber.
[0017] The preparation process of silane coupling agent modified zirconium phosphate is as follows: by weight, 3-5 parts of zirconium phosphate and 1 part of silane coupling agent are reacted in a mixed solvent of 20-30 parts of ethanol and water in a volume ratio of 6-8:1 at 20-30°C for 8-12 hours, and then filtered and dried to obtain silane coupling agent modified zirconium phosphate.
[0018] In the flame-retardant nylon 6 fiber with a skin-core structure as described above, the mass percentage of the charring agent in the skin layer is 6-10%.
[0019] The preparation process of the high-temperature self-crosslinking agent for the flame-retardant nylon 6 fiber with a skin-core structure as described above is as follows: adding the reaction raw materials, the solvent, and the catalyst into a reactor, stirring until completely dissolved, reflux reacting at 80-160° C. for 3-6 hours, and then post-treating (cooling to room temperature, adding deionized water, stirring for 30 minutes, standing for 2 hours, filtering, washing the filter cake with deionized water and ethanol alternately for 3 times, and drying the filter cake in a vacuum oven at 80° C. for 12-24 hours) to obtain the high-temperature self-crosslinking agent;
[0020] The reaction raw material is a conjugated structure monomer, and the structural formula of the conjugated structure monomer is as follows:
[0021] ;
[0022] In the formula, one of R1-R5 is -COOH or -COOR', R' is an alkyl chain with 1-3 carbon atoms; R is -N=N-, -C=N- or -C=C-; R6-R 10 At least one of them is -OH, and the rest are -H;
[0023] Alternatively, the reaction raw material is a mixture of a conjugated structure monomer and a diol (one of ethylene glycol and 1,3-propylene glycol) in a molar ratio of 1:1, and the structural formula of the conjugated structure monomer is as follows:
[0024] ;
[0025] In the formula, one of R1-R5 is -COOH or -COOR', R' is an alkyl chain having 1 to 3 carbon atoms; R is -N=N-, -C=N- or -C=C-; R 11 -R 15 At least one of them is -COOH, and the rest are -H;
[0026] The solvent is DMF, DMSO, THF or toluene;
[0027] The catalyst is one or more of benzenesulfonic acid, p-toluenesulfonic acid, EDCI (1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride), DMAP (4-dimethylaminopyridine), and HOBT (1-hydroxybenzotriazole);
[0028] The mass of the conjugated structure monomer is 10-15% of the total mass of the conjugated structure monomer and the solvent, and the mass of the catalyst is 0.5-3% of the mass of the conjugated structure monomer.
[0029] The high-temperature self-crosslinking agent of the present invention is an oligomer with high thermal stability. It will not thermally decompose or self-crosslink in a processing temperature window below 300°C (for example, the blending melting temperature, the temperature of each zone of the screw, and the temperature of the drafting roller during spinning processing) (the temperature at which the high-temperature self-crosslinking agent of the present invention undergoes a self-crosslinking reaction is 340-350°C). It can be added to a nylon 6 matrix as an additive without destroying the regularity of the molecular chain of nylon 6 itself, that is, without affecting the subsequent processing of nylon 6.
[0030] In the flame-retardant nylon 6 fiber with a skin-core structure as described above, the mass percentage of the high-temperature self-crosslinking agent in the core layer is 5-15%.
[0031] A flame-retardant nylon 6 fiber with a skin-core structure as described in any of the above items, the limiting oxygen index of the flame-retardant nylon 6 fiber with a skin-core structure is 29-33%, the vertical burning grade is V-0, and the breaking strength is 4.3-4.9 cN / dtex.
[0032] The present invention also provides a method for preparing the flame-retardant nylon 6 fiber with a skin-core structure as described above, comprising the following steps:
[0033] (1) melt-blending a carbonizing agent with nylon 6 to obtain a skin layer material, and at the same time, melt-blending a high-temperature self-crosslinking agent with nylon 6 to obtain a core layer material;
[0034] (2) The skin layer raw material and the core layer raw material are spun according to a composite spinning process to obtain a skin-core structure flame-retardant nylon 6 fiber.
[0035] As the preferred technical solution:
[0036] In the above method, during the spinning process, the temperature control of each zone of the screw is crucial to ensure the uniformity of the mixture and the stability of the melt. The temperatures of each zone of the screw corresponding to the skin material are: zone 1 245-265°C, zone 2 245-265°C, zone 3 250-270°C, zone 4 265-275°C, zone 5 275-285°C, zone 6 275-285°C, and the box temperature is 255-265°C;
[0037] The temperatures of the screw zones corresponding to the core layer materials are: Zone 1 245-265°C, Zone 2 245-265°C, Zone 3 250-270°C, Zone 4 265-275°C, Zone 5 275-285°C, Zone 6 275-285°C, and the box temperature is 255-265°C;
[0038] Four pairs of drafting rollers are used for drafting, the temperature of the first pair of drafting rollers is 80-120°C, the temperature of the second pair of drafting rollers is 130-150°C, the temperature of the third pair of drafting rollers is 180-200°C, the temperature of the fourth pair of drafting rollers is 200-240°C, and the total drafting multiple is 4.5-5.0;
[0039] The spinning speed of the first pair of drafting rollers is 600-700m / min, the spinning speed of the second pair of drafting rollers is 2.25-2.5 times that of the first pair of drafting rollers, the spinning speed of the third pair of drafting rollers is 1.6-2 times that of the second pair of drafting rollers, and the spinning speed of the fourth pair of drafting rollers is 1.0-1.2 times that of the third pair of drafting rollers.
[0040] Beneficial effects:
[0041] (1) The present invention introduces a charring agent into the cortex and a new high-temperature self-crosslinking agent into the core layer through a unique skin-core structure design. The charring agent in the cortex can form a stable char layer in a high-temperature environment, effectively blocking the penetration of flames and heat, and achieving charring flame retardancy. The new high-temperature self-crosslinking agent in the core layer self-crosslinks at high temperatures, thereby enhancing the structural stability and thermal stability of the fiber, reducing the risk of breakage and molten dripping in the event of a fire, and improving the anti-melt dripping flame retardancy. Ultimately, the combined effects of charring flame retardancy and anti-melt dripping flame retardancy significantly improve the flame retardancy.
[0042] (2) The skin-core structure flame-retardant nylon 6 fiber of the present invention not only improves the flame retardant properties, but also maintains the original high strength and other mechanical properties of nylon 6 fiber, meeting the demand of modern industry for high-performance flame-retardant fibers, and is particularly suitable for industries that have strict requirements on both flame retardant properties and mechanical properties, such as aerospace, automotive interiors, architectural decoration, and personal protective equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 is a two-dimensional XRD test diagram of the skin-core structure flame-retardant nylon 6 fiber of Example 1;
[0044] Figure 2 is a schematic structural diagram of a longitudinal section of a flame-retardant nylon 6 fiber with a sheath-core structure according to Example 1;
[0045] Figure 3 This is a two-dimensional XRD test diagram of the skin-core structure nylon 6 fiber of comparative example 1;
[0046] Figure 4 1 is a schematic structural diagram of the longitudinal section of the sheath-core nylon 6 fiber of comparative example 1. DETAILED DESCRIPTION
[0047] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0048] The following are the test methods for the relevant performance indicators in each embodiment and comparative example:
[0049] (1) Thermal stability: Thermogravimetric analyzer is used for testing, with a temperature range of 30-800°C, a heating rate of 10°C / min, and an air atmosphere. The test results are required to meet the thermal weight loss T 1% >300℃(T 1% >300℃ means: as the temperature rises, the mass of the test substance will decompose and decay, and above 300℃, only 1% of the mass will decay, and the thermal stability is good).
[0050] (2) Limiting oxygen index: tested in accordance with GB / T 2406.2-2009.
[0051] (3) Vertical burning grade: Tested according to test method B-vertical burning test of GB / T 2408-2008.
[0052] (4) Breaking strength: Tested in accordance with GB / T 14344-2008.
[0053] (5) Two-dimensional X-ray diffraction test: A two-dimensional X-ray diffractometer (Bruker, Germany, model D8DISCOVER) was used for the test. The test conditions were: test voltage 40 kV, current 40 mA, incident X-ray wavelength 1.5418×10 -10 m, select Still (VANTEC 500) for scan type, Step (with count limit) for scan step, and the effective scan time is 210s.
[0054] In the various embodiments and comparative examples of the present invention, the raw material products with the indicated manufacturers and brands are only used in the embodiments and comparative examples, and such products from other manufacturers and other brands are also feasible.
[0055] Example 1
[0056] A method for preparing a flame-retardant nylon 6 fiber with a skin-core structure, the specific steps are as follows:
[0057] (I) preparing raw materials;
[0058] Zirconium phosphate;
[0059] Silane coupling agent: γ-methacryloxypropyltrimethoxysilane;
[0060] Ethanol;
[0061] Deionized water;
[0062] Mixed solvent: a mixture of ethanol and deionized water in a volume ratio of 6:1;
[0063] Conjugated structure monomer: 4'-hydroxyazobenzene-4-carboxylic acid, CAS: 2497-38-3, the structural formula is as follows:
[0064] ;
[0065] Solvent A: DMF;
[0066] Catalyst: benzenesulfonic acid;
[0067] Nylon 6: The manufacturer is China Petrochemical Group Baling Petrochemical Co., Ltd., the brand is BL3280H;
[0068] (II) preparing a carbon-forming agent and a high-temperature self-crosslinking agent respectively;
[0069] By weight, 3 parts of zirconium phosphate and 1 part of silane coupling agent are reacted in 20 parts of a mixed solvent at 20° C. for 8 hours, and then filtered and dried to obtain silane coupling agent-modified zirconium phosphate as a carbon-forming agent;
[0070] Add conjugated monomer, solvent A and catalyst into the reactor, stir until completely dissolved, reflux at 80°C for 6 hours, cool to room temperature, add deionized water, stir for 30 minutes, stand for 2 hours, filter, wash the filter cake with deionized water and ethanol alternately for 3 times, and dry the filter cake in a vacuum oven at 80°C for 12 hours to obtain a high-temperature self-crosslinking agent. The crosslinking reaction temperature of the high-temperature self-crosslinking agent is higher than the melting point of nylon 6, higher than the spinning processing temperature, and lower than the combustion temperature of nylon 6; the thermal weight loss T of the high-temperature self-crosslinking agent is 1% 370℃;
[0071] The mass of the conjugated structure monomer is 10% of the total mass of the conjugated structure monomer and solvent A, and the mass of the catalyst is 0.5% of the mass of the conjugated structure monomer;
[0072] (III) preparing the skin layer raw material and the core layer raw material respectively;
[0073] The carbon-forming agent is melt-blended with nylon 6 to obtain a skin layer raw material, wherein the mass percentage of the carbon-forming agent in the skin layer raw material is 6%;
[0074] The high temperature self-crosslinking agent is melt-blended with nylon 6 to obtain a core layer material, wherein the mass percentage of the high temperature self-crosslinking agent in the core layer material is 5%;
[0075] (IV) Preparation of flame-retardant nylon 6 fiber with skin-core structure;
[0076] The skin layer raw material and the core layer raw material are spun according to a composite spinning process to obtain a skin-core structure flame-retardant nylon 6 fiber;
[0077] During the spinning process, the temperatures of the screw zones corresponding to the cortex raw materials were: zone 1 245°C, zone 2 245°C, zone 3 250°C, zone 4 265°C, zone 5 275°C, zone 6 275°C, and the box temperature was 255°C;
[0078] The temperatures of the screw zones corresponding to the core material are: zone 1 245°C, zone 2 245°C, zone 3 250°C, zone 4 265°C, zone 5 275°C, zone 6 275°C, and the box temperature is 255°C;
[0079] Four pairs of drafting rollers are used for drafting, the temperature of the first pair of drafting rollers is 80°C, the temperature of the second pair of drafting rollers is 130°C, the temperature of the third pair of drafting rollers is 180°C, the temperature of the fourth pair of drafting rollers is 200°C, and the total drafting multiple is 4.5;
[0080] The spinning speed of the first pair of drafting rollers is 600m / min, the spinning speed of the second pair of drafting rollers is 2.25 times the spinning speed of the first pair of drafting rollers, the spinning speed of the third pair of drafting rollers is 2 times the spinning speed of the second pair of drafting rollers, and the spinning speed of the fourth pair of drafting rollers is 1.0 times the spinning speed of the third pair of drafting rollers.
[0081] The base material of the finally prepared skin-core structure flame-retardant nylon 6 fiber is nylon 6 with a specification of 50D / 36F, and the ratio of the thickness of the skin layer to the diameter of the core layer is 1:6; the charring agent is only located in the skin layer, and the charring agent is orderly and directional arranged along the axial direction of the skin-core structure flame-retardant nylon 6 fiber, and the high-temperature self-cross-linking agent is only located in the core layer; the limiting oxygen index of the skin-core structure flame-retardant nylon 6 fiber is 29%, the vertical burning grade is V-0, and the breaking strength is 4.9cN / dtex.
[0082] Comparative Example 1
[0083] A method for preparing a sheath-core structured nylon 6 fiber is basically the same as in Example 1, except that step (IV) does not use four pairs of drafting rollers for drafting, but only pre-oriented yarns.
[0084] The two-dimensional X-ray diffraction test results of the skin-core nylon 6 fiber prepared in this comparative example are as follows: Figure 3 As shown in the figure, there is a bright ring at the arrow point, indicating that the carbon-forming agent is not arranged in a directional manner. At this time, the arrangement of the carbon-forming agent is as follows Figure 4 shown.
[0085] The limiting oxygen index of the core-skin structure nylon 6 fiber obtained in this comparative example is 27%, the vertical burning grade is V-1, and the breaking strength is 3.2 cN / dtex. Compared with Example 1, the limiting oxygen index of Example 1 decreases, the vertical burning grade decreases, and the breaking strength decreases. This is because the carbon-forming agent of Example 1 is not orderly oriented along the axial direction of the fiber, resulting in poor improvement of the flame retardant performance, and the mechanical properties are significantly reduced due to the lack of stretching by multiple pairs of stretching rollers; while in Example 1, as the fiber is stretched and oriented by multiple pairs of stretching rollers, the carbon-forming agent with a lamellar structure is also orderly arranged to form an orderly oriented arrangement along the axial direction of the fiber. This structure is conducive to charring and smoke suppression, and improves the flame retardant effect. The two-dimensional X-ray diffraction test results of the core-skin structure flame-retardant nylon 6 fiber of Example 1 are shown as follows: Figure 1 As shown in the figure, the arrow is a shortened and brightened arc, indicating that the carbon-forming agent is orderly arranged along the axial direction of the fiber. At this time, the arrangement of the carbon-forming agent is as follows Figure 2 As shown, this is because the carbon-forming agent with a lamellar structure is promoted to be orderly oriented along the axial direction of the fiber during the fiber drawing process.
[0086] By comparing the flame retardant performance data and breaking strength as well as the two-dimensional X-ray diffraction test results of Example 1 and Comparative Example 1, it can be seen that the orderly directional arrangement of the carbon-forming agent along the axial direction of the fiber has an important influence on the flame retardant properties and mechanical strength of the skin-core structure flame retardant nylon 6 fiber.
[0087] Comparative Example 2
[0088] A method for preparing a nylon 6 fiber with a sheath-core structure is basically the same as that in Example 1, except that a carbon-forming agent is added to both the sheath layer raw material and the core layer raw material in step (III), the carbon-forming agent is evenly distributed in the sheath layer and the core layer, and the mass percentage of the carbon-forming agent in the sheath layer raw material and the core layer raw material is 6%.
[0089] The breaking strength of the obtained nylon 6 fiber with skin-core structure is 4.0 cN / dtex. Compared with Example 1, the breaking strength performance of Comparative Example 2 is significantly reduced, because the carbonizing agent is an inorganic powder, and adding both the skin layer and the core layer will reduce the overall breaking strength, but in Example 1, only the carbonizing agent is added to the skin layer, and the breaking strength can still be maintained by the core layer.
[0090] Comparative Example 3
[0091] A method for preparing a nylon 6 fiber with a skin-core structure is basically the same as that in Example 1, except that in step (III), the core layer raw material is only nylon 6 and there is no high-temperature self-crosslinking agent.
[0092] The obtained skin-core structure nylon 6 fiber has a limiting oxygen index of 26% and a vertical combustion grade of V-2. Compared with Example 1, the limiting oxygen index of Comparative Example 3 decreases, and the vertical combustion grade decreases. This is because the flame retardant effect of the carbonizing agent in the skin layer alone cannot achieve the purpose of anti-droplet, and the core layer will still melt and form droplets during the combustion process. At the same time, the droplets formed by the core layer will also destroy the carbon layer formed in the skin layer, affecting the improvement of the flame retardant performance.
[0093] Comparative Example 4
[0094] A method for preparing a nylon 6 fiber with a sheath-core structure is basically the same as that in Example 1, except that in step (III), a high-temperature self-crosslinking agent is added to both the sheath layer raw material and the core layer raw material, the high-temperature self-crosslinking agent is evenly distributed in the sheath layer and the core layer, and the mass percentage of the high-temperature self-crosslinking agent in the sheath layer raw material and the core layer raw material is 5%.
[0095] The obtained skin-core structure nylon 6 fiber has a limiting oxygen index of 27% and a vertical combustion grade of V-2. Compared with Example 1, the limiting oxygen index of Comparative Example 4 decreases and the vertical combustion grade decreases. This is because if the high-temperature self-crosslinking agent is evenly distributed in the skin layer and the core layer, the high-temperature self-crosslinking agent itself will also burn as a combustible during the combustion process, which will affect the carbonization of the skin layer and the quality of the carbon layer when the fiber burns, and cannot play its anti-melting droplet function, which is also unfavorable to the improvement of flame retardant properties.
[0096] Comparative Example 5
[0097] A method for preparing a nylon 6 fiber with a skin-core structure is basically the same as that in Example 1, except that the skin layer is too thick, and the ratio of the thickness of the skin layer to the diameter of the core layer is 1:2.
[0098] The vertical burning grade of the obtained core-skin structure nylon 6 fiber is V-2. Compared with Example 1, the vertical burning grade of Comparative Example 5 is lowered because the skin layer does not have the function of anti-melting droplets. If the skin layer is too thick, the skin layer will melt under the flame to form droplets.
[0099] Comparative Example 6
[0100] A method for preparing a nylon 6 fiber with a skin-core structure is basically the same as that in Example 1, except that the skin layer is too thin, and the ratio of the thickness of the skin layer to the diameter of the core layer is 1:10.
[0101] The vertical burning rating of the obtained sheath-core nylon 6 fiber is V-1. Compared with Example 1, the vertical burning rating of Comparative Example 6 is lowered because the skin layer is too thin, which causes the heat to be transferred to the core layer too quickly, causing the core layer to melt faster than the crosslinking reaction of the high-temperature self-crosslinking agent, thereby affecting the anti-droplet flame retardant effect.
[0102] Example 2
[0103] A method for preparing a flame-retardant nylon 6 fiber with a skin-core structure, the specific steps are as follows:
[0104] (I) Preparation of raw materials;
[0105] Zirconium phosphate;
[0106] Silane coupling agent: γ-methacryloxypropyltrimethoxysilane;
[0107] Ethanol;
[0108] Deionized water;
[0109] Mixed solvent: a mixture of ethanol and deionized water in a volume ratio of 6:1;
[0110] Conjugated monomer: 4-(4-hydroxy-azobenzene) ethyl benzoate, CAS: 4418-89-7, the structural formula is as follows:
[0111] ;
[0112] Solvent A: DMSO;
[0113] Catalyst: p-toluenesulfonic acid;
[0114] Nylon 6: The manufacturer is China Petrochemical Group Baling Petrochemical Co., Ltd., the brand is BL3280H;
[0115] (II) preparing a carbon-forming agent and a high-temperature self-crosslinking agent respectively;
[0116] By weight, 3 parts of zirconium phosphate and 1 part of silane coupling agent are reacted in 20 parts of a mixed solvent at 20° C. for 8 hours, and then filtered and dried to obtain silane coupling agent-modified zirconium phosphate as a carbon-forming agent;
[0117] Add conjugated monomer, solvent A and catalyst into the reactor, stir until completely dissolved, reflux at 100°C for 5h, cool to room temperature, add deionized water, stir for 30min, let stand for 2h, filter, wash the filter cake with deionized water and ethanol alternately for 3 times, dry the filter cake in a vacuum oven at 80°C for 18h, and obtain a high-temperature self-crosslinking agent. The crosslinking reaction temperature of the high-temperature self-crosslinking agent is higher than the melting point of nylon 6, higher than the spinning processing temperature, and lower than the combustion temperature of nylon 6; the thermal weight loss T of the high-temperature self-crosslinking agent is 1% 355℃;
[0118] The mass of the conjugated structure monomer is 11% of the total mass of the conjugated structure monomer and solvent A, and the mass of the catalyst is 0.5% of the mass of the conjugated structure monomer;
[0119] (III) preparing the skin layer raw material and the core layer raw material respectively;
[0120] The carbon-forming agent is melt-blended with nylon 6 to obtain a skin layer raw material, wherein the mass percentage of the carbon-forming agent in the skin layer raw material is 7%;
[0121] The high temperature self-crosslinking agent is melt-blended with nylon 6 to obtain a core layer material, wherein the mass percentage of the high temperature self-crosslinking agent in the core layer material is 7%;
[0122] (IV) Preparation of flame-retardant nylon 6 fiber with skin-core structure;
[0123] The skin layer raw material and the core layer raw material are spun according to a composite spinning process to obtain a skin-core structure flame-retardant nylon 6 fiber;
[0124] During the spinning process, the temperatures of the screw zones corresponding to the cortex raw materials were: zone 1 255°C, zone 2 255°C, zone 3 255°C, zone 4 265°C, zone 5 275°C, zone 6 275°C, and the box temperature was 260°C;
[0125] The temperatures of the screw zones corresponding to the core material are: zone 1 250°C, zone 2 250°C, zone 3 255°C, zone 4 265°C, zone 5 275°C, zone 6 275°C, and the box temperature is 260°C;
[0126] Four pairs of drafting rollers are used for drafting, the temperature of the first pair of drafting rollers is 90°C, the temperature of the second pair of drafting rollers is 135°C, the temperature of the third pair of drafting rollers is 185°C, the temperature of the fourth pair of drafting rollers is 210°C, and the total drafting multiple is 4.5;
[0127] The spinning speed of the first pair of drafting rollers is 600m / min, the spinning speed of the second pair of drafting rollers is 2.25 times the spinning speed of the first pair of drafting rollers, the spinning speed of the third pair of drafting rollers is 2 times the spinning speed of the second pair of drafting rollers, and the spinning speed of the fourth pair of drafting rollers is 1.0 times the spinning speed of the third pair of drafting rollers.
[0128] The base material of the finally prepared skin-core structure flame-retardant nylon 6 fiber is nylon 6 with a specification of 50D / 36F. The ratio of the thickness of the skin layer to the diameter of the core layer is 1:6. The skin layer contains a charring agent with a lamellar structure and the charring agent is only located in the skin layer. The charring agent is orderly and directional arranged along the axial direction of the skin-core structure flame-retardant nylon 6 fiber, and the high-temperature self-cross-linking agent is only located in the core layer; the limiting oxygen index of the skin-core structure flame-retardant nylon 6 fiber is 30%, the vertical burning grade is V-0, and the breaking strength is 4.7cN / dtex.
[0129] Example 3
[0130] A method for preparing a flame-retardant nylon 6 fiber with a skin-core structure, the specific steps are as follows:
[0131] (I) Preparation of raw materials;
[0132] Zirconium phosphate;
[0133] Silane coupling agent: γ-glycidyloxypropyltrimethoxysilane;
[0134] Ethanol;
[0135] Deionized water;
[0136] Mixed solvent: a mixture of ethanol and deionized water in a volume ratio of 7:1;
[0137] Conjugated structure monomer: 4-((4-carboxybenzylidene)amino)benzoic acid, CAS: 2243913-03-1, the structural formula is as follows:
[0138] ;
[0139] Ethylene glycol;
[0140] Solvent A: DMSO;
[0141] Catalyst: EDCI;
[0142] Nylon 6: The manufacturer is China Petrochemical Group Baling Petrochemical Co., Ltd., the brand is BL3280H;
[0143] (II) preparing a carbon-forming agent and a high-temperature self-crosslinking agent respectively;
[0144] By weight, 3 parts of zirconium phosphate and 1 part of silane coupling agent are reacted in 25 parts of a mixed solvent at 25° C. for 10 hours, and then filtered and dried to obtain silane coupling agent-modified zirconium phosphate as a carbon-forming agent;
[0145] A mixture of conjugated structure monomer and ethylene glycol in a molar ratio of 1:1, solvent A, and catalyst are added to a reactor, stirred until completely dissolved, refluxed at 120°C for 4 hours, cooled to room temperature, added with deionized water, stirred for 30 minutes, allowed to stand for 2 hours, filtered, the filter cake was washed alternately with deionized water and ethanol for 3 times, and the filter cake was placed in a vacuum oven at 80°C and dried for 18 hours to obtain a high-temperature self-crosslinking agent. The crosslinking reaction temperature of the high-temperature self-crosslinking agent is higher than the melting point of nylon 6, higher than the spinning processing temperature, and lower than the combustion temperature of nylon 6; the thermal weight loss T of the high-temperature self-crosslinking agent is 1% 345℃;
[0146] The mass of the conjugated structure monomer is 12% of the total mass of the conjugated structure monomer and solvent A, and the mass of the catalyst is 1.5% of the mass of the conjugated structure monomer;
[0147] (III) preparing the skin layer raw material and the core layer raw material respectively;
[0148] The carbon-forming agent is melt-blended with nylon 6 to obtain a skin layer raw material, wherein the mass percentage of the carbon-forming agent in the skin layer raw material is 8%;
[0149] The high temperature self-crosslinking agent is melt-blended with nylon 6 to obtain a core layer material, wherein the mass percentage of the high temperature self-crosslinking agent in the core layer material is 9%;
[0150] (IV) Preparation of flame-retardant nylon 6 fiber with skin-core structure;
[0151] The skin layer raw material and the core layer raw material are spun according to a composite spinning process to obtain a skin-core structure flame-retardant nylon 6 fiber;
[0152] During the spinning process, the temperatures of the screw zones corresponding to the skin material were: zone 1 260°C, zone 2 260°C, zone 3 260°C, zone 4 270°C, zone 5 280°C, zone 6 280°C, and the box temperature was 260°C;
[0153] The temperatures of the screw zones corresponding to the core material are: zone 1 255°C, zone 2 255°C, zone 3 260°C, zone 4 270°C, zone 5 280°C, zone 6 280°C, and the box temperature is 260°C;
[0154] Four pairs of drafting rollers are used for drafting, the temperature of the first pair of drafting rollers is 100°C, the temperature of the second pair of drafting rollers is 140°C, the temperature of the third pair of drafting rollers is 190°C, the temperature of the fourth pair of drafting rollers is 220°C, and the total drafting multiple is 4.8;
[0155] The spinning speed of the first pair of drafting rollers is 650m / min, the spinning speed of the second pair of drafting rollers is 2.5 times that of the first pair of drafting rollers, the spinning speed of the third pair of drafting rollers is 1.6 times that of the second pair of drafting rollers, and the spinning speed of the fourth pair of drafting rollers is 1.2 times that of the third pair of drafting rollers.
[0156] The final skin-core structure flame-retardant nylon 6 fiber has a base material of nylon 6 with a specification of 100D / 72F. The ratio of the thickness of the skin layer to the diameter of the core layer is 1:7. The skin layer contains a charring agent with a lamellar structure and the charring agent is only located in the skin layer. The charring agent is orderly and directional arranged along the axial direction of the skin-core structure flame-retardant nylon 6 fiber, and the high-temperature self-cross-linking agent is only located in the core layer. The limiting oxygen index of the skin-core structure flame-retardant nylon 6 fiber is 32%, the vertical burning grade is V-0, and the breaking strength is 4.6 cN / dtex.
[0157] Example 4
[0158] A method for preparing a flame-retardant nylon 6 fiber with a skin-core structure, the specific steps are as follows:
[0159] (I) Preparation of raw materials;
[0160] Zirconium phosphate;
[0161] Silane coupling agent: γ-glycidyloxypropyltrimethoxysilane;
[0162] Ethanol;
[0163] Deionized water;
[0164] Mixed solvent: a mixture of ethanol and deionized water in a volume ratio of 8:1;
[0165] Conjugated structure monomer: 4,4-dicarboxydiphenylethylene, CAS: 100-31-2, the structural formula is as follows:
[0166] ;
[0167] 1,3-Propanediol;
[0168] Solvent A: THF;
[0169] Catalyst: DMAP;
[0170] Nylon 6: The manufacturer is China Petrochemical Group Baling Petrochemical Co., Ltd., the brand is BL3280H;
[0171] (II) preparing a carbon-forming agent and a high-temperature self-crosslinking agent respectively;
[0172] By weight, 4 parts of zirconium phosphate and 1 part of silane coupling agent are reacted in 25 parts of a mixed solvent at 25° C. for 10 hours, and then filtered and dried to obtain silane coupling agent-modified zirconium phosphate as a carbon-forming agent;
[0173] A mixture of a conjugated structure monomer and 1,3-propylene glycol in a molar ratio of 1:1, solvent A, and a catalyst are added to a reactor, stirred until completely dissolved, refluxed at 140°C for 4 hours, cooled to room temperature, added with deionized water, stirred for 30 minutes, allowed to stand for 2 hours, filtered, and the filter cake was washed alternately with deionized water and ethanol for 3 times. The filter cake was placed in a vacuum oven at 80°C and dried for 24 hours to obtain a high-temperature self-crosslinking agent. The crosslinking reaction temperature of the high-temperature self-crosslinking agent is higher than the melting point of nylon 6, higher than the spinning processing temperature, and lower than the combustion temperature of nylon 6; the thermal weight loss T 1% 340℃;
[0174] The mass of the conjugated structure monomer is 13% of the total mass of the conjugated structure monomer and solvent A, and the mass of the catalyst is 1.5% of the mass of the conjugated structure monomer;
[0175] (III) preparing the skin layer raw material and the core layer raw material respectively;
[0176] The carbon-forming agent is melt-blended with nylon 6 to obtain a skin layer raw material, wherein the mass percentage of the carbon-forming agent in the skin layer raw material is 9%;
[0177] The high temperature self-crosslinking agent is melt-blended with nylon 6 to obtain a core layer material, wherein the mass percentage of the high temperature self-crosslinking agent in the core layer material is 11%;
[0178] (IV) Preparation of flame-retardant nylon 6 fiber with skin-core structure;
[0179] The skin layer raw material and the core layer raw material are spun according to a composite spinning process to obtain a skin-core structure flame-retardant nylon 6 fiber;
[0180] During the spinning process, the temperatures of the screw zones corresponding to the skin material were: 260°C in zone 1, 260°C in zone 2, 265°C in zone 3, 270°C in zone 4, 285°C in zone 5, 285°C in zone 6, and the box temperature was 265°C;
[0181] The temperatures of the screw zones corresponding to the core material are: zone 1 260°C, zone 2 260°C, zone 3 265°C, zone 4 270°C, zone 5 280°C, zone 6 280°C, and the box temperature is 265°C;
[0182] Four pairs of drafting rollers are used for drafting, the temperature of the first pair of drafting rollers is 110°C, the temperature of the second pair of drafting rollers is 145°C, the temperature of the third pair of drafting rollers is 195°C, the temperature of the fourth pair of drafting rollers is 230°C, and the total drafting multiple is 4.8;
[0183] The spinning speed of the first pair of drafting rollers is 650m / min, the spinning speed of the second pair of drafting rollers is 2.5 times that of the first pair of drafting rollers, the spinning speed of the third pair of drafting rollers is 1.6 times that of the second pair of drafting rollers, and the spinning speed of the fourth pair of drafting rollers is 1.2 times that of the third pair of drafting rollers.
[0184] The final skin-core structure flame-retardant nylon 6 fiber has a base material of nylon 6 with a specification of 100D / 72F. The ratio of the thickness of the skin layer to the diameter of the core layer is 1:7. The skin layer contains a charring agent with a lamellar structure and the charring agent is only located in the skin layer. The charring agent is orderly and directional arranged along the axial direction of the skin-core structure flame-retardant nylon 6 fiber, and the high-temperature self-cross-linking agent is only located in the core layer. The limiting oxygen index of the skin-core structure flame-retardant nylon 6 fiber is 32%, the vertical burning grade is V-0, and the breaking strength is 4.5cN / dtex.
[0185] Example 5
[0186] A method for preparing a flame-retardant nylon 6 fiber with a skin-core structure, the specific steps are as follows:
[0187] (I) Preparation of raw materials;
[0188] Zirconium phosphate;
[0189] Silane coupling agent: γ-glycidyloxypropyltrimethoxysilane;
[0190] Ethanol;
[0191] Deionized water;
[0192] Mixed solvent: a mixture of ethanol and deionized water in a volume ratio of 8:1;
[0193] Conjugated structure monomer: 2-(p-hydroxyphenylazo)benzoic acid, CAS: 1634-82-8, its structural formula is as follows:
[0194] ;
[0195] Solvent A: toluene;
[0196] Catalyst: HOBT;
[0197] Nylon 6: The manufacturer is China Petrochemical Group Baling Petrochemical Co., Ltd., the brand is BL3280H;
[0198] (II) preparing a carbon-forming agent and a high-temperature self-crosslinking agent respectively;
[0199] By weight, 5 parts of zirconium phosphate and 1 part of silane coupling agent are reacted in 30 parts of a mixed solvent at 30° C. for 12 hours, and then filtered and dried to obtain silane coupling agent-modified zirconium phosphate as a carbon-forming agent;
[0200] Add conjugated monomer, solvent A and catalyst into the reactor, stir until completely dissolved, reflux at 160°C for 3h, cool to room temperature, add deionized water, stir for 30min, stand for 2h, filter, wash the filter cake with deionized water and ethanol alternately for 3 times, dry the filter cake in a vacuum oven at 80°C for 24h, and obtain a high-temperature self-crosslinking agent. The crosslinking reaction temperature of the high-temperature self-crosslinking agent is higher than the melting point of nylon 6, higher than the spinning processing temperature, and lower than the combustion temperature of nylon 6; the thermal weight loss T of the high-temperature self-crosslinking agent is 1% 330℃;
[0201] The mass of the conjugated structure monomer is 15% of the total mass of the conjugated structure monomer and solvent A, and the mass of the catalyst is 3% of the mass of the conjugated structure monomer;
[0202] (III) preparing the skin layer raw material and the core layer raw material respectively;
[0203] The carbon-forming agent is melt-blended with nylon 6 to obtain a skin layer raw material, wherein the mass percentage of the carbon-forming agent in the skin layer raw material is 10%;
[0204] The high temperature self-crosslinking agent is melt-blended with nylon 6 to obtain a core layer material, wherein the mass percentage of the high temperature self-crosslinking agent in the core layer material is 15%;
[0205] (IV) Preparation of flame-retardant nylon 6 fiber with skin-core structure;
[0206] The skin layer raw material and the core layer raw material are spun according to a composite spinning process to obtain a skin-core structure flame-retardant nylon 6 fiber;
[0207] During the spinning process, the temperatures of the screw zones corresponding to the cortex raw materials were: zone 1 265°C, zone 2 265°C, zone 3 270°C, zone 4 275°C, zone 5 285°C, zone 6 285°C, and the box temperature was 265°C;
[0208] The temperatures of the screw zones corresponding to the core material are: zone 1 265°C, zone 2 265°C, zone 3 270°C, zone 4 275°C, zone 5 285°C, zone 6 285°C, and the box temperature is 265°C;
[0209] Four pairs of drafting rollers are used for drafting, the temperature of the first pair of drafting rollers is 120°C, the temperature of the second pair of drafting rollers is 150°C, the temperature of the third pair of drafting rollers is 200°C, the temperature of the fourth pair of drafting rollers is 240°C, and the total drafting multiple is 5.0;
[0210] The spinning speed of the first pair of drafting rollers is 700m / min, the spinning speed of the second pair of drafting rollers is 2.5 times the spinning speed of the first pair of drafting rollers, the spinning speed of the third pair of drafting rollers is 2 times the spinning speed of the second pair of drafting rollers, and the spinning speed of the fourth pair of drafting rollers is 1.0 times the spinning speed of the third pair of drafting rollers.
[0211] The final skin-core structure flame-retardant nylon 6 fiber has a base material of nylon 6 with a specification of 150D / 96F. The ratio of the thickness of the skin layer to the diameter of the core layer is 1:8. The skin layer contains a charring agent with a lamellar structure and the charring agent is only located in the skin layer. The charring agent is orderly and directional arranged along the axial direction of the skin-core structure flame-retardant nylon 6 fiber, and the high-temperature self-cross-linking agent is only located in the core layer. The limiting oxygen index of the skin-core structure flame-retardant nylon 6 fiber is 33%, the vertical burning grade is V-0, and the breaking strength is 4.3cN / dtex.
[0212] It can be seen from Examples 1 to 5 that the thermal weight loss T of the high temperature self-crosslinking agent prepared by the present invention is 1% The flame retardant nylon 6 fiber with skin-core structure prepared by the present invention has a limiting oxygen index of ≥29%, a vertical combustion grade of V-0, and excellent flame retardant performance; a breaking strength of ≥4.3cN / dtex, and excellent mechanical properties.
Claims
1. A flame-retardant nylon 6 fiber with a skin-core structure, wherein the base material is nylon 6, characterized in that: It contains a carbon-forming agent with a lamellar structure and a high-temperature self-crosslinking agent; the carbon-forming agent is only located in the skin layer, and the carbon-forming agent is orderly and directional arranged along the axial direction of the skin-core structure flame-retardant nylon 6 fiber; The high-temperature self-crosslinking agent is only located in the core layer; the crosslinking reaction temperature of the high-temperature self-crosslinking agent is higher than the melting point of nylon 6 and lower than the combustion temperature of nylon 6; the specification of the skin-core structure flame-retardant nylon 6 fiber is 50-150D / 36-96F, and the ratio of the thickness of the skin layer to the diameter of the core layer is 1:6-8; The carbon-forming agent is zirconium phosphate modified by a silane coupling agent; The preparation process of the high temperature self-crosslinking agent is as follows: adding the reaction raw materials, solvent and catalyst into a reaction kettle, stirring until completely dissolved, reflux reaction at 80-160° C. for 3-6 hours, and post-processing to obtain the high temperature self-crosslinking agent; The reaction raw material is a conjugated structure monomer, and the structural formula of the conjugated structure monomer is as follows: In the formula, one of R1-R5 is -COOH or -COOR', R' is an alkyl chain having 1 to 3 carbon atoms; R is -N=N-, -C=N- or -C=C-; R6-R 10 At least one of them is -OH, and the rest are -H; The catalyst is at least one of benzenesulfonic acid, p-toluenesulfonic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 4-dimethylaminopyridine, and 1-hydroxybenzotriazole.
2. The flame-retardant nylon 6 fiber with a skin-core structure according to claim 1, characterized in that: The preparation process of the silane coupling agent modified zirconium phosphate is as follows: by weight, 3-5 parts of zirconium phosphate and 1 part of silane coupling agent are reacted in a mixed solvent of 20-30 parts of ethanol and water in a volume ratio of 6-8:1 at 20-30° C. for 8-12 hours, and then filtered and dried to obtain the silane coupling agent modified zirconium phosphate; The silane coupling agent is γ-methacryloxypropyltrimethoxysilane or γ-glycidyloxypropyltrimethoxysilane.
3. The flame-retardant nylon 6 fiber with a skin-core structure according to claim 2, characterized in that: The mass percentage of the carbon-forming agent in the cortex is 6-10%.
4. The flame-retardant nylon 6 fiber with a skin-core structure according to claim 1, characterized in that: The reaction raw material is a mixture of a conjugated structure monomer and a diol in a molar ratio of 1:
1. The structural formula of the conjugated structure monomer is as follows: In the formula, one of R1-R5 is -COOH or -COOR', R' is an alkyl chain having 1 to 3 carbon atoms; R is -N=N-, -C=N- or -C=C-; R 11 -R 15 At least one of them is -COOH and the rest are -H.
5. The flame-retardant nylon 6 fiber with a skin-core structure according to claim 4, characterized in that: The mass percentage of the high temperature self-crosslinking agent in the core layer is 5-15%.
6. A flame-retardant nylon 6 fiber with a skin-core structure according to any one of claims 1 to 5, characterized in that: The limiting oxygen index of the skin-core structure flame-retardant nylon 6 fiber is 29-33%, the vertical burning grade is V-0, and the breaking strength is 4.3-4.9 cN / dtex.
7. A method for preparing a flame-retardant nylon 6 fiber with a skin-core structure as claimed in claim 1, characterized in that: The following steps are involved: (1) melt-blending a carbon-forming agent with nylon 6 to obtain a skin layer material, and at the same time, melt-blending a high-temperature self-crosslinking agent with nylon 6 to obtain a core layer material; (2) The skin layer raw material and the core layer raw material are spun according to a composite spinning process to obtain a skin-core structure flame-retardant nylon 6 fiber.
8. The method according to claim 7, characterized in that During the spinning process, the temperatures of the screw zones corresponding to the skin material are: zone 1 245-265°C, zone 2 245-265°C, zone 3 250-270°C, zone 4 265-275°C, zone 5 275-285°C, zone 6 275-285°C, and the box temperature is 255-265°C; The temperatures of the screw zones corresponding to the core layer materials are: Zone 1 245-265°C, Zone 2 245-265°C, Zone 3 250-270°C, Zone 4 265-275°C, Zone 5 275-285°C, Zone 6 275-285°C, and the box temperature is 255-265°C; Four pairs of drafting rollers are used for drafting, the temperature of the first pair of drafting rollers is 80-120°C, the temperature of the second pair of drafting rollers is 130-150°C, the temperature of the third pair of drafting rollers is 180-200°C, the temperature of the fourth pair of drafting rollers is 200-240°C, and the total drafting multiple is 4.5-5.0; The spinning speed of the first pair of drafting rollers is 600-700m / min, the spinning speed of the second pair of drafting rollers is 2.25-2.5 times that of the first pair of drafting rollers, the spinning speed of the third pair of drafting rollers is 1.6-2 times that of the second pair of drafting rollers, and the spinning speed of the fourth pair of drafting rollers is 1.0-1.2 times that of the third pair of drafting rollers.
Citation Information
Patent Citations
Azobenzene structure based high-temperature self-cross-linked expanded flame-retardant anti-dripping copolyester and preparation method thereof
CN102863611A
High-temperature resistant polyamide sheath-core composite fiber and preparation method for same
CN102534831A
Sheath-core spinning flame-retardant anti-dripping fibers and preparing method and application thereof
CN105088770A